Matching BRCA and prostate cancer in a public health system: Report of the Italian Society for Uro-Oncology (SIUrO) consensus project. (April 2023) - Lapini, Alberto; Caffo, Orazio; Conti, Giario Natale; Pappagallo, Giovanni; Del Re, Marzia; D'Angelillo, Rolando Maria; Capoluongo, Ettore Domenico; Castiglione, Francesca; Brunelli, Matteo; Iacovelli, Roberto; De Giorgi, Ugo; Bracarda, Sergio
Abstract: The recent approval of PARP inhibitors for the treatment of metastatic –castration-resistant prostate cancer (mCRPC) patients with BRCA mutations firstly introduced the possibility of proposing a targeted treatment in this disease. However, the availability of this therapeutic option raises a number of questions concerning the management of prostate cancer in everyday clinical practice: the timing and method of detecting BRCA mutations, the therapeutic implications of the detection, and the screening of the members of the family of a prostate cancer patient with a BRCA alteration. These challenging issues led the Italian Society for Uro-Oncology (SIUrO) to organise a Consensus Conference aimed to develop suggestions capable of supporting clinicians managing prostate cancer patients. The present paper described the development of the statements discussed during the consensus, which involved all of the most important Italian scientific societies engaged in the multi-disciplinary and multi-professional management of the disease. Graphical Abstract: ga1 Highlights: PARPi inhibitors are efficacious in mCRPC patients with BRCA mutations. This therapeutic opportunity raises a number of questions in the daily practice. The issues concern the detection and its therapeutic and familial implications. SIUrO organized a Consensus Conference to address these questions. Following a formal methodology, 23 statements were voted by the panellists.